Our amazing animal friends - Stuart, Gene S. (Washington, D.C. : National Geographic Society, 1990)
Introduces recordholders of the animal world, including the largest lizard and the fastest mammal
Includes bibliographical references (p. [33])
650
Keywords: Animals -- Juvenile literature; Animals